L'oblique dans le monde Grec : concept et imagerie - Girard, Thibaut (Archaeopress Publishing Ltd, 2015)
What could be more evident than the concepts of oblique, horizontal or vertical? In the modern world, these concepts form the basis of our thought system, both from a mathematical and artistic point of view. Everything would suggest that these principles were known to the Greek civilization. However, the study of the surviving texts casts a different light on the matter. Homer did not know the concept of oblique - no word could translate it into the language of his time. Even later, the Greeks had five adjectives approximately meaning oblique. Each discipline (cosmology, optic, geography, art, etc.) had its own way of looking at these five words. This work examines this topic.